Multimodal Discourse Analysis of Sumenep Tourism Guidebook for Lombang Beach - Noor, Suriansyah Abdillah; Ekawati, Rosyida (STAI Nurul Islam Mojokerto, 2025)
This study aims to conduct a multimodal discourse analysis of the Sumenep tourism guidebook to understand how verbal and visual elements contribute to its overall promotional effectiveness. The emphasis is on identifying and analyzing these elements to uncover the underlying meanings conveyed through the guidebook. It adopts a qualitative approach, employing discourse analysis methods to examine both visual and verbal elements present in the guidebook. Data collection involved gathering various segments of the guidebook, which were then subjected to a detailed analysis to uncover how these elements interact to form cohesive messages. The theoretical framework used for analysis is based on Kress Leeuwen's Multimodal Discourse Analysis (MDA). The findings reveal that the guidebook effectively employs a combination of verbal and visual elements to promote Lombang beach tourism. These elements work to construct appealing and persuasive messages that attract potential tourists. The study concludes that MDA is a useful tool for understanding the complex interplay between different modes of communication in promotional materials.